Government helper and citizen advocate? A case study of the multiple roles and pressures facing a nongovernmental organization contracted by government to strengthen community health in northern India. (24th November 2017) - Scott, Kerry; George, Asha S.; Harvey, Steven A.; Mondal, Shinjini; Patel, Gupteswar; VR, Raman; Sheikh, Kabir
Summary: While nongovernmental organizations (NGOs) can potentially strengthen valuable citizen political engagement, NGOs that are increasingly oriented towards donor and government contracts may instead contribute to depoliticizing development. Amidst competing pressures, NGO experiences and agency in managing multiple roles require examination. We present a qualitative case study of an NGO implementing a government‐designed intervention to strengthen Village Health, Sanitation, and Nutrition Committees (VHSNCs) in rural north India. Despite a challenging context of community scepticism and poor government services, the NGO did successfully form VHSNCs by harnessing its respected interlocutor status, preexisting relationships, and ability to "sell" the VHSNC as a mechanism for improving local well‐being. While the VHSNC enabled community members to voice concerns to government officials, improvements often failed to meet community expectations. NGO staff endured community frustration on one hand and rebuffs from lower‐level officials on the other, while feeling undersupported by the government contract. Consequently, although contracted to strengthen a community institution, the NGO increasingly worked alongside VHSNC members to try to strengthen the public sector. Contrary to assumptions that NGOs become "tamed" through taking government contracts, being contracted to deliver inputs for community participation was intertwined with microlevel political action, though this came at a cost to the NGO.